Politicians' promotion incentives and bank risk exposure in China - Li Wang; Lukas Menkhoff; Michael Schröder; Xian Xu (Frankfurt School of Finance & Management, 2015)
This paper shows that politicians' pressure to climb the career ladder increases bank risk exposure in their region. Chinese local politicians are set growth targets in their region that are relative to each other. Growth is stimulated by debt-financed programs which are mainly financed via bank loans. The stronger the performance incentive the riskier the respective local bank exposure becomes. This effect holds primarily for local banks which are under a certain degree of control of local politicians and it has increased with the release of recent stimulus packages requiring local co-financing.
Keywords: G21; G23; H74; 330; Bank Lending; Bank Risk Exposure; Local Politicians; Promotion Incentives